The salinity tolerance of some Eastern Province fish in relation to their known distribution - Hofmeyr, Hendrik Petrus (Rhodes University, Faculty of Science, Department of Zoology, 1966)
The tolerances to sea water, sodium chloride and sodium sulphate of various cichlid, cyprinid and anabantid species which occur naturally in or near the Eastern Province region of Southern Africa, were determined, and correlated with their distribution ranges. Of the nine freshwater species tested, only Tilapia mossambica is able to disperse through the sea and is therefore the only member of the secondary division (Myers 1937) present in this region. The remaining species are possibly all limited to the use of freshwater links for dispersal between river systems. Death of fish in sea water and in sodium chloride is chiefly due to loss of osmotic control, but in solutions of sodium sulphate a pronounced toxic effect is responsible for death. In all the solutions used, an inverse relation between survival time and concentration is present. No evidence of any cells specialised for salt excretion was found in the gills of fish exposed to various salt concentrations.
Keywords: Uncatalogued